The Relationship between Compensation and Benefits Management on Employee Well-being: A Study of Malaysian SMEs in Johor - Foo, Shuan Yap; Salahudin, Shahrul Nizam (Research in Management of Technology and Business, 2025)
The objective of this study is to explore the relationship between satisfaction with compensation and benefits management and employees’ well-being in small and medium-sized enterprises (SMEs) in Johor, Malaysia. A quantitative methodology was employed, gathering data through structured surveys administered to employees across various SMEs. The data was analysed using descriptive and inferential statistical methods with tools such as the Statistical Package for Social Sciences (SPSS). The findings reveal a significant positive relationship between satisfaction with compensation and benefits management and employees’ well-being. The study highlights that competitive compensation packages and effective benefits management can enhance employee well-being, reduce workplace stress, and improve job satisfaction. These insights offer valuable guidance for SME managers and policymakers in designing strategies to optimise compensation structures, implement comprehensive benefit schemes, and foster a supportive work environment. Practical implications include the development of fair compensation systems, employee wellness programs, and policies that align organisational goals with employee needs to ensure sustainable success.